Public-Private health sector mix-way forward - D.L. Buso (South African Family Practice)
The debate on Public-Private mix has been around in South Africa (SA) for the past ten years. The debate arose out of a realisation of the weaknesses in the public health parallel with the ever-increasing private sector worldwide. The concept has been referred to in different terminologies, public-private mix, public private partnerships (PPP), public private initiatives (PPI). This paper aims to stimulate further debate on the subject, in the light of changing policies and political thinking in the country. The paper presents findings and examples from other countries, based on a review of literature on the subject. The paper concludes that in SA there is a strong potential for public private mixing, but warns that the process should be carefully implemented.